Retrograde intra-renal surgery (RIRS) A minimally invasive technology, gaining progressive popularity in Renal Stone Management (Bangladesh Journal of Urology, 2025)
Retrograde intra-renal surgery (RIRS) has become an effective and safe treatment modality in the management of renal stone diseases In 1987, Bagley first introduced RIRS and reported the results of a flexible RIRS procedure1.Recent developments and innovations in the flexible ureterorenoscope and auxiliary equipment have made this procedure easier and more effective with increased success rates. RIRS can be used as a primary treatment in patients with renal stones around 2 cm, prior unsuccessful shock wave lithotripsy, infundibular stenosis, renoureteral malformation, skeletal-muscular deformity, bleeding diathesis and obese patients.Training for RIRS, fluoroscopy use, the concurrent or simultaneous use of RIRS in the treatment of various modalities like ESWL (Extracorporial shock wave lithotripsy), PCNL (Percutaneous nephrolithotomy) etc. may be needed2.preoperative assessment, possible stone free rate, the cost of this modality with probable auxiliary procedure need to be discussed with the patient and relatives are extremely important prior the procedure.Bangladesh J. Urol. 2025; 28(1): 39-43